Does Neuraxial Anesthesia as General Anesthesia Damage DNA? A Pilot Study in Patients Undergoing Orthopedic Traumatological Surgery - Kucharova, Monika; Astapenko, David; Zubanova, Veronika; Koscakova, Maria; Stetina, Rudolf; Zadak, Zdenek; Hronek, Miloslav (International journal of molecular sciences, 2019)
The human organism is exposed daily to many endogenous and exogenous substances that are the source of oxidative damage. Oxidative damage is one of the most frequent types of cell component damage, leading to oxidation of lipids, proteins, and the DNA molecule. The predominance of these damaging processes may later be responsible for human diseases such as cancer, neurodegenerative disease, or heart failure. Anesthetics undoubtedly belong to the group of substances harming DNA integrity. The goal of this pilot study is to evaluate the range of DNA damage by general and neuraxial spinal anesthesia in two groups of patients undergoing orthopedic traumatological surgery. Each group contained 20 patients, and blood samples were collected before and after anesthesia; the degree of DNA damage was evaluated by the comet assay method. Our results suggest that general anesthesia can cause statistically significant damage to the DNA of patients, whereas neuraxial anesthesia has no negative influence.
Keywords: dospělí; DNA Damage; Female; Adult; ženské pohlaví; ortopedické výkony; DNA; lidé; Anesthesia, General; Pilot Projects; celková anestezie; pilotní projekty; poškození DNA; Orthopedic Procedures; Male; Comet Assay; Aged; kometový test; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans